Study of the Tribological Behavior of the Textured Steel Coated with TMD Films - MAHADESHWARA, Manoj RAJANKUNTE (2022)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia